IMPLEMENTASI MODEL PEMBELAJARAN BLENDED LEARNING PADA MATA PELAJARAN PAI DI SMA NEGERI 2 MALANG - Siti Aisiyah (VICRATINA, 2022)
The purpose of this study is to describe how the Blended learning Model was implemented. The blended learningmodel is a combination of traditional and electronic learning where initially traditional learning only uses a face-to-face model, but with time and current conditions, as well as the development of technology, learning has gone on to use electronic forms. Online and a combination of the two learning models is called blended learning. This research uses a qualitative approach with the type of case study research. This research was carried out in SMA Negeri 2 Malang due to the fact that the schools that implemented this learning model saw the situation and conditions during the pandemic so far that required alternative learning, i.e. face-to-face and online learning. But not only that, the learning model in SMA Negeri 2 Malang is also done if offline or face-to-face learning is done, but the teacher provides material or assignments through online means, it is also called blended learning model or blended. learning. The results of the application of the blended learning model are 1) The students' interest in learning is increasing because the learning system is not monotonous and cannot be in turns. 2) The effectiveness of offline or offline learning time can facilitate and shorten teachers' time because teachers can provide material through online application means and also provide homework 3) Digital literacy of teachers students is more widespread because they do not learn through books but they can through the Internet and students can learn anytime and anywhere, not necessarily at school.